HARNESSING POWERSAS SIMULATION MODELING FOR ADVANCING PROFICIENCIES IN POWER SYSTEM IN CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Cross River State, Nigeria, endowed with abundant renewable energy resources, faces persistent electricity challenges that hinder socio-economic development. This study explores the application of PowerSAS simulation modeling to enhance power system proficiencies, focusing on small hydropower (SHP) potential in the state’s hilly regions. Utilizing a primary data collection approach through field surveys and stakeholder interviews, we assessed demographic profiles, energy needs, and system performance across six Local Government Areas (LGAs). PowerSAS was employed to simulate power generation scenarios, optimizing energy output and cost-efficiency. Findings indicate that Kwa Falls, Kundeve, and Ajasor streams hold significant SHP potential, with a combined capacity of 20 MW during peak seasons. The study highlights the model’s ability to integrate demographic data and site-specific parameters to improve system reliability. Challenges such as funding and infrastructure gaps were identified, underscoring the need for policy reforms. Recommendations include capacity building for local engineers and public-private partnerships to scale SHP projects. This research provides a framework for leveraging simulation tools to address Nigeria’s energy crisis sustainably.